2000
DOI: 10.1002/1521-4141(200011)30:11<3309::aid-immu3309>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients with X-linked lymphoproliferative disease have a defect in 2B4 receptor-mediated NK cell cytotoxicity

Abstract: A significant breakthrough in the nitride chemistry of main group elements has been achieved: Surprisingly Sn3N4, for which there had been no proof of existence until now, as well as the isotypic high‐pressure polymorphs γ‐Si3N4 and γ‐Ge3N4 have been synthesized. All three compounds crystallize in a spinel structure type (see picture) that previously has not been found for nitrides, and may have a high relevance for practical applications in the context of ultrahard materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 42 publications
9
102
2
Order By: Relevance
“…These studies suggested a “lack of function” of 2B4 31 32. Further studies should clarify these divergent results and in particular whether they reflect a heterogeneity of the patients phenotype or other yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggested a “lack of function” of 2B4 31 32. Further studies should clarify these divergent results and in particular whether they reflect a heterogeneity of the patients phenotype or other yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A dramatically altered function of 2B4 has recently been detected in individuals affected by the X-linked lymphoproliferative disease (XLP [28, 31, 32]). XLP is a severe inherited immune deficiency, characterized by the inability to control EBV infection resulting in fulminant infectious mononucleosis or lymphoma 33 34.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in NK cells derived from these patients both CD244 and NTBA have been shown transduce abnormal inhibitory signals resulting in sharp inhibition of cytotoxicity against EBV-infected cells [1,[19][20][21]. This may contribute to the pathogenesis and to the progression of the disease since B-EBV-infected cells are characterized by high levels of expression of CD244-and NTBA-specific ligands, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the absence of SH2D1A molecule, the interaction of CD244 and NTBA with their ligands on EBVinfected cells has been shown to transduce inhibitory signals that render XLP-NK cells unable to kill EBVinfected targets [19][20][21]. While the ligand recognized by CD244, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Ligationinduced phosphorylation of 2B4 recruits intracellular proteins that include PI3K and SLAM-associated protein (SAP) 3 to its cytoplasmic domain, thus initiating a signaling cascade, substantial elements of which are unknown (6, 10 -14). Mutations of SAP, an intracellular adaptor protein containing a single Src homology SH2 domain, are associated with the fatal disorder X-linked lymphoproliferative (XLP) disease (15)(16)(17) and NK cells from XLP patients lack normal function when stimulated through 2B4 (10,12,13,18,19). Although the precise physiologic functions of SAP in NK cells remain unknown, it is thought that this protein competes with SH2 protein tyrosine phosphatases for binding to tyrosinephosphorylated 2B4 thus preventing the delivery of negative signals through 2B4 (16).…”
Section: Role For Glycogen Synthase Kinase-3 In Nk Cellmentioning
confidence: 99%